Pengaruh Gaya Hidup Halal terhadap Preferensi Konsumen dalam Memilih Produk Ritel Syariah - Riana Tirsya; A. Rasikhu Z. Haramain (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of a halal lifestyle on consumer preferences in selecting Sharia-compliant retail products. The study employed a Systematic Literature Review method, reviewing various empirical and conceptual studies published between 2017 and 2025. The analysis focused on the relationship between halal awareness, religiosity, ethical consumption values, and Muslim consumer behavior in making choices about Sharia-compliant retail products and services. The results indicate that a halal lifestyle is viewed not only as a form of compliance with Islamic law but also as a social identity and a modern consumption pattern that influences consumer purchasing decisions. Consumers with high levels of halal awareness and religiosity tend to have a greater preference for Sharia-compliant retail products that guarantee halal certification, quality, transparency, and ethical values ​​in their business processes. Furthermore, trust, Islamic brand image, and marketing strategies based on Islamic values ​​contribute to strengthening consumer loyalty to Sharia-compliant retail. This research provides managerial implications for Sharia-compliant retail businesses to develop innovative, educational, and tailored marketing strategies to meet the halal lifestyle needs of modern Muslims.